Effect of low-temperature treatments on photoluminescence enhancement of ion-beam synthesized Si nanocrystals in SiO₂ matrix - Khatsevich, I.; Melnik, V.; Popov, V.; Romanyuk, B.; Fedulov, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The results of experimental researches of photoluminescence (PL) spectra in
Si nanocluster structures obtained by implantation of silicon ions to SiO₂-Si structures
with high-temperature (1100 °C) and following low-temperature annealings in various
regimes are given. We have found that additional low-temperature treatments in definite
regimes result in substantial increase of the PL intensity, thus a maximum effect is
observed after annealing in air. The possible mechanisms of the obtained effects are
discussed. Those are based on supposition about the dominating contribution of
luminescence through the electronic states on SiO₂-Si nanoclaster interfaces, which is
related to defect and impurity complexes. It has been shown that growth of the PL
intensity is governed by two effects: generation of new centers of radiative
recombination on the nanocrystal-dielectric matrix interfaces, and passivation of nonradiative
recombination centers.